(untitled) (Tanzania Medical Journal, 2020)
Background Breast cancer is the second leading cancer among women in Tanzania accounting for about 3,000 cases and 1,300 deaths in 2018 alone. National Cancer treatment guidelines have been developed addressing management of patients with breast cancer. How current practice will need to change to conform to new guideline has not been investigated. Evidence is needed to understand how much changes will be needed to affect changes needed. Objectives This study sought to understand how breast cancer patients at Muhimbili National Hospital are investigated and assigned to treatment. Methodology A cross-sectional descriptive study was carried out among patients with breast cancer who underwent modified radical mastectomy at Muhimbili National Hospital in 2018. Consent was obtained and patient’s demography, clinical characteristics, investigations and treatment assignment was collected. Descriptive statistics were computed where proportions were used for categorical variables and means with standard deviations for age. Results A total of 80 patients with mean age of 49.9 (SD 13.5) years were involved. Fine Needle Aspiration Cytology was diagnostic in 19 (23.8%). Immunohistochemistry was not available before surgery and requested only in 60(70%). Regarding clinical status 65 (81.3%) of the patients were clinical stage III disease with only 58 (72.5) receiving neo-adjuvant therapy. None of the patients had mammography or CT scan done. Conclusion We have demonstrated that BC management at MNH is not concordant with any known international treatment guidelines. Furthermore, Multi Disciplinary Team approach is critically lacking and needs to be well defined if the new treatment guidelines were to be effective. Recommendation Improvement in Breast Cancer Management needs to embrace the concept of Multi Disciplinary Team approach. Key words: Breast Cancer, Investigations, Traetment Guidelines.